Fermentation of Fructooligosaccharides by Lactic Acid Bacteria and Bifidobacteria - Kaplan, Handan (American Society for Microbiology, 2000)
Lactic acid bacteria and bifidobacteria were screened of their ability to ferment fructooligosaccharides (FOS) on MRS agar. Of 28 strains of lactic acid bacteria and bifidobacteria examined, 12 of 16 Lactobacillus strains and 7 of 8 Bifidobacterium strains fermented FOS. Only strains that gave a positive reaction by the agar method reached high cell densities in broth containing FOS.